2000
DOI: 10.1088/0268-1242/15/8/307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between n-type and p-type Al/SiNx:H/In0.53Ga0.47As devices deposited by electron cyclotron resonance technique

Abstract: The influence of the semiconductor doping type over the electrical properties of Al/SiN x :H/In 0.53 Ga 0.47 As metal-insulator-semiconductor (MIS) devices has been studied using capacitance-voltage (C-V ) and current-voltage (I -V ) measurements. The C-V data show that the SiN x :H/p-In 0.53 Ga 0.47 As interface is more defective than the SiN x :H/n-In 0.53 Ga 0.47 As one. In both n-and p-type MIS structures, the interface trap density (D it ), the electrical breakdown field (E B ) and the resistivity (ρ) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…23 Figures 10͑a͒ and 10͑b͒ present both C q and C h C -V curves of SiN x :H/p-In 0.53 Ga 0.47 As and SiN x :H/n-In 0.53 Ga 0. 47 As interfaces, respectively, where the insulator film was deposited with a gas flux ratio of Rϭ5 ͑i.e., xϭ1.5).…”
Section: Alõsin X :Hõin 053 Ga 047 As Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Figures 10͑a͒ and 10͑b͒ present both C q and C h C -V curves of SiN x :H/p-In 0.53 Ga 0.47 As and SiN x :H/n-In 0.53 Ga 0. 47 As interfaces, respectively, where the insulator film was deposited with a gas flux ratio of Rϭ5 ͑i.e., xϭ1.5).…”
Section: Alõsin X :Hõin 053 Ga 047 As Devicesmentioning
confidence: 99%
“…17 In this article, we analyze in detail the influence of the RTA on the physical properties of ECR deposited SiN x :H films in a wide range of compositions-from Si-rich films to N-rich-and analyze the RTA effects on the SiN x :H/semiconductor interface with Si, [19][20][21] In 0.53 Ga 0. 47 As, 22,23 and InP. 24 -27 II.…”
mentioning
confidence: 99%
“…Hence, it is highly desirable to identify also oxygen free dielectrics that provide high quality interfaces with InGaAs. Previous studies of the silicon nitride / n-type InGaAs interface have not demonstrated Fermi level de-pinning (5), and probably due to these unfavorable results this dielectric was abandoned in favor of ALD oxides-based passivation layers. Here, we revisit the Si 3 N 4 / InGaAs interface, and demonstrate that thermal treatment reduces the defect interface traps and that Fermi level de-pinning is achieved.…”
Section: Introductionmentioning
confidence: 98%
“…(iii) Rapid thermal annealing (RTA) treatments of the MIS structure obtained in the two ways described above. This approach has been widely studied by our group in SiN x :H/Si [12,13], SiN x :H/InGaAs [14,15] and SiN x :H/InP [16] structures, where it has been proven that the RTA treatments with temperatures between 500-700 • C, depending on the substrate, improve the whole performance of the devices.…”
Section: Introductionmentioning
confidence: 99%